Bibliometrics in Public Administration - Marques, Tânia M. G. (2020)
Introduction: Bibliometrics refers to the studies which seek to compute the processes of written communication, including several methods for tracking the scientific information on a discipline, a field, or a topic. Thus, bibliometrics make available a complementary perspective of the history, path, and evolution of a discipline through the quantitative analysis of its existent literature. In Public Administration, there is arguably a scarcity of bibliometric studies. The relevance and usefulness of the bibliometric approach has not been yet fully grasped by the Public Administration scholars. Thus, an advancement on this comprehension and a widespread use of bibliometric techniques may contribute to advance the research in the Public Administration discipline.